SIKAP PETANI TERHADAP GABUNGAN KELOMPOK TANI (GAPOKTAN) - Yunus Puratmoko; Kusnandar Kusnandar; Arip Wijianto (AGRITEXTS: Journal of Agricultural Extension, 2016)
This research aim to study farmer’s attitude to Gapoktan, studying farmer’s former factors for attitude to Gapoktan and study the relation between farmer’s former factors for attitude with its attitude to Gapoktan. Basic method used by quantitative research method with survay technique. Research location determined by purposive that is in District of Banyudono Sub Province Boyolali. Withdrawal of sample done by Stratified Random Sampling, chosen three Countryside they were Tanjungsari, Banyudono and Batan. After obtained by countryside is later taken by proportional random sampling, for the farmer sample a number of 40 by Random. Type and data source cover primary data and sekunder data. Analysis method used to know the farmer’s former factor for attitude and farmer’s attitude to Gapoktan is class wide formula. While to test relation between farmer’s former factors for attitude with its attitude to Gapoktan use Rank Spearman correlation analysis.Result of research indicate that farmer’s attitude to Gapoktan pertained goodness. From result of Rank Spearman analysis and significance test at trust level 95% personal experience do not significant with farmer’s attitude to Gapoktan assess correlation coefficient (-0,174). While lionized others influence (0,443), formal education (0,442) and of non formal education (0,469), or significant and correlate positive with farmer’s attitude to Gapoktan.